El uso del internet en los estudiantes de séptimo año de educación básica de la escuela Pompilio Reinoso Jaramillo de Sauces Norte de la ciudad de Loja periodo 2014-2015”. Lineamientos alternativos - Japón Chimbo, María Natalia (2016)
In this thesis entitled EL USO DEL INTERNET EN LOS ESTUDIANTES DE SEPTIMO AÑO DE EDUCACIÓN BÁSICA DE LA ESCUELA POMPILIO REINOSO JARAMILLO DE SAUCES NORTE DE LA CIUDA DE LOJA PERIODO 2014-2015”. LINEAMIENTOS ALTERNATIVOS, was established as a central problem do you determine the interaction between students and internet seventh year of education through the use that give the same? This research has the general objective: To determine how Internet use by students in the seventh year of basic education school Pompilio Reinoso Jaramillo North of the city of Loja Sauces. Inductive, deductive, statistical, and analytical methods used, also observing techniques and survey of teachers and students in the seventh year of basic school education Pompilio Reinoso were applied. Field research was conducted with the participation of 27 seventh-grade students, 6 teachers and the Director of the school. A proposal for a training plan was applied to solve the inappropriate use of the Internet by students in the seventh grade of primary school education Pompilio Reinoso Jaramillo North Sauces City Loja, 2014-2015. The survey of students could be obtained as a result that 100 % of children use the Internet, where it has been evidence has decreased activities as sports by 22 %; hanging out with friends at 7%, 22% in studying, doing reading libros11 %, and 11% make reading newspapers, preferring to use technology. In the survey of teachers it was learned that 100 % believe that use of the internet and say it is important for the development of student learning.